Legal Study on Withdrawal of Fiduciary Guarantee Based on the Decision of the Constitutional Court Number 2/PUU-XIX/2021 - Rizal Nugra Wijaya; Rusdianto Sesung (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2022)
The practice of withdrawing fiduciary guarantees by financing institutions has often caused controversy because each party has a legal basis that can be used to maintain the goods resulting in the use of physical force to be able to withdraw fiduciary guarantee goods. These ways of withdrawal eventually became a problem in society so that it extended into problems related to human rights violations. That resulted in the emergence of a request for a material test of Law No. 42 of 1999 on Fiduciary, especially in Article 15 paragraphs (2) and (3) and then the Constitutional Court issued Decree No. 18 / PUU-XVII / 2019 about Fiduciary especially in Article 15 paragraphs (2) and (3) and then the Constitutional Court issued Decree No. 18 / PUU-XVII / 2019 which contains that there must be an agreement between the debtor and creditors about the state of default and for that then the debtor is authorized to withdraw the fiduciary guarantee or willingly release the fiduciary guarantee item, if there is no agreement and willingness then the withdrawal order must be through a court ruling. Because it is considered that the verdict provides injustice on the creditor's side, it is further submitted a material test of the court's decision, and through The Court's Decision No. 2/PUU-XIX/2021, the Court stated that it rejected the request for a material test and upheld the previous verdict. Based on this, this study will legally review how the withdrawal of fiduciary guarantee goods based on the ruling and as a conclusion is the withdrawal that can be made by creditors against fiduciary guarantee goods are: (a) Make an agreement with the debtor where the debtor voluntarily submits the fiduciary guarantee to the creditor, for sale through auction. The terms of the sale are prohibited to harm the debtor, i.e. if the selling price is below the value of debit debt; (b) Request a verdict to the judge to be able to execute the item based on the registered fiduciary certificate, and for the next sale of the fiduciary guarantee at auction. If it is not done as such then the creditor is at risk of being reported as a criminal delik with Article 362 of KUHP for attempted theft (if the taking of the goods is unknown to the owner of the goods) and/or Article 368 of the Criminal Code on attempts to confiscate the property of others.